PENGANTAR RANCANGAN MODUL PELATIHAN MANAJEMEN WAKTU PADA HIMPUNAN MAHASISWA PROGRAM STUDI PSIKOLOGI UNIVERSITAS “X” - Linda Linda (Universitas Bunda Mulia, 2017)
As an undergraduate, the activity of lectures and the organization becomes a learning event for working. Problem arises when they have difficulty regulating time between lectures and organizational activities. However, this can be overcome by developing time management skills through training as a form of intervention. The introduction to time management training module design is based on active training approach that uses the principles of experiential learning. At University “X”, specifically at the program of study of Psychology, time management skills in the undergraduate association program measured using a scale of time management that consists of 15 item created by researcher with the range of validity 0,405 – 0,876 and reliability 0,889. The result is from 27 undergraduate, 17 have time management skills that tend to be low and 10 tend to be high. However the introduction to the design of training modules produced in this study has its limitation. It still needs further development on the next research in order to design a holistic training module of time management, which effectiveness can be tested more accurately. Keywords: time management, training module, active training, experiential learning.